High‐Loading Carbon Nanotube/Polymer Nanocomposite Fabric Coatings Obtained by Capillarity‐Assisted "Excess Assembly" for Electromagnetic Interference Shielding. Issue 13 (26th April 2018) - Lan, Chuntao; Li, Chenglong; Hu, Jiyong; Yang, Shuguang; Qiu, Yiping; Ma, Ying
Abstract: This work presents the fabrication of high‐loading carbon nanotube (CNT)/polymer nanocomposite coatings via capillarity‐assisted assembly on fabrics for electromagnetic interference (EMI) shielding. The nanocomposite coatings formed by step‐by‐step assembly on fabrics possess a CNT loading as high as 70.9 wt%. The assistance of the capillary force in the textile increases the mass of CNTs deposited on the fabric by two orders of magnitude compared to that deposited through common electrostatic assembly. The coated fabrics thus exhibit a good EMI shielding effectiveness of 11.9 dB, indicating their capability to resist 92.7% of electromagnetic irradiation. Moreover, the nanocomposite coatings are only micrometers thick, so the coated fabrics are soft, flexible, and air permeable. In this work, a simple, scalable, and versatile method is developed to fabricate effective EMI shielding coatings on fabrics. Capillarity‐assisted assembly, which is highly controllable, represents an attractive strategy to construct high‐efficiency EMI shielding coatings through composition optimization of coatings. Abstract : High‐loading carbon nanotube (CNT)/polymer nanocomposite coatings for electromagnetic interference (EMI) shielding are constructed on fabrics by capillarity‐assisted assembly. The assembled fabrics exhibit a good EMI shielding effectiveness of 11.9 dB as a result of their high CNT loading (70.9 wt%) and the dramatically increased deposition of CNTs on fabrics, which is achieved through the assistance of capillarity in the fabric.